Advancing Patient Safety Through the Clinical Application of a Framework Focused on Communication. Issue 8 (31st December 2021) - Manojlovich, Milisa; Hofer, Timothy P.; Krein, Sarah L.
Abstract : Objectives: The study of communication has evolved from diverse academic disciplines, yet those diverse fields are not well represented in theoretical frameworks that describe communication in health care, narrowing our ability to explain how communication affects patient safety. The purpose of this review article is to describe a conceptual framework of communication drawn from multiple academic disciplines and apply it to health care, specifically for examining communication between providers about the clinical care of their patients. Methods: A seminal article in the field of communication that attempted to map the entire field of communication theory inspired our conceptual framework. We adapted these concepts, largely from the social science literature, to find alternative ways of conceptualizing communication and ways to enhance communication in health care. Results: There are 8 theoretical traditions that informed our conceptual framework: rhetorical, phenomenological, semiotic, cybernetic, sociopsychological, sociocultural, critical, and pragmatic. We provide practical, clinical applications of our conceptual framework, encompassing the interpersonal nature of communication, relationship building and trust, hierarchical differences, and the role of technology in communication. In adopting our conceptual framework, we suggest that researchers and clinicians can choose from any combination of these 8 theoretical traditions to more fully describe and ultimately enhance communication-related phenomena. Conclusions: Poor communication remains a stubborn problem in health care in part because of a narrow theoretical and definitional approach to resolving it. Our conceptual framework suggests ways to build relationships and trust, addresses hierarchical differences between communicators, and illuminates the role of technology in communication. It also importantly expands the definition of the value of communication beyond simple information exchange to include creation of new knowledge during communication through the development of shared understanding.